Excess deaths from COVID-19 correlate with age and socio-economic status. A database study in the Stockholm region. (1st October 2020) - Strang, Peter; Fürst, Per; Schultz, Torbjörn
Abstract: Background: The COVID-19 pandemic has affected the entire health care system, internationally as well as in Sweden. We aimed to study excess deaths (all death causes, but also COVID-19-related deaths) during the COVID-19 pandemic regarding age, socio-economic status, the situation in nursing homes, and place of death for nursing home residents. Design: We performed a descriptive regional registry data study using VAL, the Stockholm Regional Council's central data warehouse, which covers almost all health care use in the county of Stockholm. T tests and chi-square tests were used for comparisons. Results: Compared with 2016–2019, there were excess deaths in March–May 2020 ( p  < 0.0001), mainly explained by COVID-19, but in April there were also unexplained excess deaths. Individuals dying from COVID-19 were older than patients dying from other causes ( p  < 0.0001). There were more patient deaths among people residing in less advantaged socio-economic areas ( p  < 0.0001). Nursing home residents dying from COVID-19 were more often admitted to acute hospitals than residents dying from other causes ( p  < 0.0001). Also, the proportion of admissions of nursing home residents dying from other causes increased from April to May 2020 ( p  < 0.0001). Conclusions: Dying from COVID-19 mainly affects the elderly, nursing home residents, and persons from less advantaged socio-economic groups. The pandemic has resulted in an increase in acute admissions of dying nursing home residents to acute hospitals.